Growth and Stock Of Swamp Buffalo (Buballus buballis) in Kuantan District, Kuansing Regency, Riau Province - Yendraliza Yendraliza; Muhammad Arifsyah; Dewi Ananda Mucra; Elfawati Elfawati (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The purpose of this study was to know the population structure, natural increase, net replacement stock, and output of buffalo, as well as the holding capacity and capacity of breeders in managing the buffalo. The research was conducted in 14 villages based on the largest number of buffalo population. The material of this research was buffalo (1,802 heads) and buffalo breeders with a total of 179 respondents. The parameters measured were population structure, natural increase, net replacement rate (NRR), output, area carrying capacity and livestock ability to raise. Data were analyzed descriptively by displaying the mean and standard deviation. The results showed that the population structure was dominated by female 68.03%, natural increase 34.74%, male NRR 145.10%; female NRR 310.61%, output 16.83%. the carrying capacity of the Kuantan Tengah area was 10,685.67 ST with the ability of 45.58% breeders. Conclusion: Buffalo cattle in Central Kuantan District have high productivity and Central Kuantan District could be used as a source area for buffalo seedlings.